Analysis of electric field strength propagating underneath the 132 kV overhead power line - B. Alhaj, Reyad Mohamed (2013)
This research presents the electric field strength propagating of 132 kV overhead power lines. In the calculation of the electric field with the charge simulation method it is difficult to judge the magnitude of the field strength in the area, especially the accuracy of the field strength. One of the applications of electric field strength is its implementation in radio planning process as an accurate estimation of propagating power loss. This provides a way for determination of the electric field strength carrier-to-interference (C/I) ratio and all other parameters necessary for proper radio design, to know the effects of electric field on human health. 132 kV overhead lines have selected to be the case of study in this project because this type used to be in the area which near the residential area that nowadays mostly being occupied with commercial, offices, building, housing estates etc. The objectives of this study to define the possible method enabling calculating the electric field strength underneath the 132 kV line, another objective is to calculate the electric field strength propagated by the 132 kV line at some points above the ground level, and analysis the finding results with the guideline electric limits public and occupational exposure as defined in the international standard. The work in this project has used Excel and Visio to discuss the analysis before getting results it has done calculate the conductor sag, conductor clearance and conductor distances for each level. The study has divided to three cases the first case analysis the electric field for single conductor, the second case analysis the electric for two conductors, the third case analysis the electric field for all six conductors, all those analyse are on 1 m and 2 m above the ground and its vicinity on 30 m left and 30 m right from the centre line. This research has compared the finding results with the EMF exposure standards with general public and occupational exposure limits the results were less than standard limits for both cases of study 1m and 2m above the ground on 30m form center the line. The results of this research shown the electric field in area on 1m and 2m above the ground at 30m left and right from center the line is enough safe.